Bioactive compounds and antioxidant capacity of African olive (Canarium schweinfurthii Engl.) Fruit pulp and Seed - Arthur Tabula; Tobias Pointner; Lili Daroczi; Pignitter Marc; Khadijah Nakyinsige; Michael Bamuwamye; Otmar Hoeglinger (Elsevier, 2026)
Abstract This study characterized polyphenols and tocopherols, as well as determined the antioxidant capacity of the Canarium schweinfurthii Engl. fruit pulp and seed. Samples were obtained from Kamuli, Luwero and Mayuge districts of Uganda. Total polyphenol content was determined using the Folin-Ciocalteu assay. Polyphenols were fractionated using Liquid Chromatography-tandem Mass Spectrometry technique. Tocopherols (α-, γ- and δ-) were quantified using High Performance Liquid Chromatography-Ultraviolet. The antioxidant capacity of the fruit pulp was assessed using Trolox Equivalent Antioxidant Capacity (TEAC) and Ferric Ion Reducing Antioxidant Power (FRAP). Total polyphenol content of the fruit pulp and seed extracts ranged from 73.93 to 92.43 and 132.66 to 146.74 mg GAE/g, respectively. The fruit pulp and seed extracts contained phenolic acids (1.3-Dicaffeoylquinic acid, 4-hydroxybenzoic acid, chlorogenic acid, ferulic acid, gallic acid, quinic acid, cinnamic acid and p-coumaric acid), flavonoids (amentoflavone, eriodictyol, gallocatechol, herbacetin and quercetin-3-O-glucoside) and lignans (pinoresinol). The tocopherol content of the fruit pulp and seed extracts was correspondingly 3.83 to 4.98 mg/kg and 38.54 to 62.47 mg/kg. The major tocopherol isomers quantified were the alpha, gamma and delta. The antioxidant capacity of the fruit pulp extracts by TEAC assay was from 2.74 to 5.43 and by FRAP assay from 4.36 to 6.16 µmol TE/g dry weight. The fruit’s antioxidant capacity may be attributable to phenolic acids, flavonoids and lignans, and tocopherols. In addition to its use as a food, the gamut of bioactives and antioxidant capacity support Canarium schweinfurthii’s potential therapeutic applications.
Keywords: Keywords: African olive Fruit pulp Seed Polyphenols Tocopherols Anti-oxidants